AR campus connect: Enhancing social connectivity through augmented reality in university settings - Tay, Min Min (2024)
This project introduces an innovative AR application called AR Campus Connect, designed to revolutionize the campus experience for Universiti Tunku Abdul Rahman (UTAR) students. The project aims to address the prevalent challenges faced by universities students, including unfamiliarity with campus structures, lack of awareness about campus events, and limited avenues for social interaction. The project adopted the incremental development model of Agile development methodology, which involved iterative cycles of specification, development and validation. Moreover, the implementation of AR technology relies on the integration of the ARCore API. Within this project, the utilization of the geospatial creator tool within ARCore facilitates the seamless placement of anchors at arbitrary coordinates. This functionality extends beyond ground-level placement, as anchors can also be positioned on buildings, enhancing the versatility of the application. By activating their phone's camera, users can effortlessly visualize anchor points on nearby buildings and access instant event-related information. Notably, the Geospatial Creator tool employs a combination of Visual Positioning Service (VPS) and Global Positioning System (GPS) data to achieve high-accuracy Geospatial poses. In instances where VPS or GPS data is unavailable, such as when the device is out of VPS range or experiencing poor GPS signal, the system seamlessly switches to utilize data from the alternate source, ensuring continued accuracy in location tracking. Furthermore, the project integrates the Google Maps SDK to provide users with instant access to their current location and UTAR building markers. The system also incorporates real-time location updates, with the user's location being refreshed every five seconds. This frequent updating ensures that users receive accurate and up-to-date information about their whereabouts, facilitating smooth navigation and exploration of the campus. AR Campus Connect also introduces two key features: Moment and Event. The Moment feature allows users to capture and share significant on-campus experiences with peers, enriching their campus life through interactive AR content. Meanwhile, the Event feature provides updates and notifications about campus happenings, ensuring students stay informed and engaged with their university community. Firebase's Cloud Firestore serves as the database solution for this project, providing a cloud-based platform for real-time data storage and retrieval. In conclusion, AR Campus Connect represents a groundbreaking solution to the challenges faced by UTAR students in navigating and engaging with their campus environment by harnessing the power of AR technology and Agile development methodologies.